Excellent aging stability of upgraded fast pyrolysis bio-oil in supercritical ethanol. (15th November 2018) - Jo, Heuntae; Verma, Deepak; Kim, Jaehoon
Graphical abstract: Highlights: Accelerated aging for 1 year was tested before and after supercritical upgrading. Fast pyrolysis bio-oil (LBFBO) was upgraded in supercritical ethanol. Upgraded bio-oil (UBO) consisted of esters, alcohols, ethers and alkylated phenols. During the 3-month aging of LBFBO, a jelly-like non-flowable phase formed. Negligible compositional changes of UBO were achieved for up to 6 months of aging. Abstract: The stabilities of low-boiling-fraction fast pyrolysis bio-oil (LBFBO) and upgraded bio-oil (UBO) produced using supercritical ethanol (scEtOH) were examined under accelerated aging conditions at 80 °C for up to 1 year. During the 3-month aging of LBFBO, a jelly-like non-flowable phase formed, and a hard, solid block formed after further aging for over 6 months. The viscosities and molecular weights of aged LBFBOs increased significantly. In contrast, the UBOs exhibited excellent stabilities after up to 6 months of aging with marginal increases in their viscosities and molecular weights. The condensation reaction during the aging of LBFBO led to the formation of water and reduced the oxygen content, while negligible changes were observed in the elemental contents of the aged UBOs. The excellent aging stability of UBO was attributed to its non- or less-reactive chemical species than those of LBFBO. Acetic acid, which acted as a catalyst for condensation and persisted for the 3-month aging of LBFBO, was converted into its corresponding ethyl ester during the scEtOH upgrading. The reactive pyrolytic lignin in LBFBO decomposed into its low-molecular-weight fractions. In addition, the other reactive species in LBFBO, such as aldehydes, furfural, and monoaromatics substituted with α, β-unsaturated aldehyde groups, were converted to less- or non-reactive species during the upgrading. Therefore, negligible compositional changes in the chemical structure of UBOs were achieved for up to 6 months of aging.